Effect of compressive stress on Fe self-diffusion in nanocrystalline FeN(Zr) thin films - Chakravarty, Sujoy; Gupta, Mukul; Schmidt, Harald; Gupta, Ajay (Diffusion Fundamentals, 2008)
In the present work the effect of compressive stress on self-diffusion of Fe in nanocrystalline FeN(Zr) alloys has been investigated. Two different types of Fe64N26Zr10 samples, one without applied stress and another with applied compressive stress of 42 GPa, were deposited under identical conditions using magnetron sputtering. The stress has been applied to the sample by bending the substrate during the deposition using a three point bending device. The self-diffusivities of Fe were determined by measuring the broadening of 57Fe marker layers by Secondary Ion Mass Spectrometry after annealing at 443 K, 483 K and 523 K for 1 hour. The activation energy and preexponential factor for Fe diffusion is comparatively higher in the stressed sample. The higher activation energy might be due to the fact that the system transforms into a more dense state when compressive stress is applied.